Working with orality in teaching practice - Leite Cavacante, Francilene; Varginha Ramos Caiado, Robertao (Revista Letras Raras, 2024)
This essay aims to discuss the speech-writing continuum in teaching practice, highlighting the representation of orality in the conversational activity. The research examines the importance of the oral modality of language in teaching, rejecting the idea that writing is superior to speech (Brasil/MEC, 1998; Marcuschi, 2010; Fávero et al., 2005). To this purpose, it analyzes pedagogical practices and textual genres, arguing that orality is an interactive social practice for communicative purposes and manifests itself in various textual genres and contexts of use. Simultaneously, it states that writing is a mode of textual-discursive production, characterized by its graphic constitution. The essay emphasizes the need to incorporate the oral modality into the various social fields and stresses the importance of expanding these practices. It concludes that there is still a lack of practices focused on orality in schools, justified by the belief that oral uses of the language are automatically acquired in everyday life. The research recommends a pedagogical approach that integrates speaking and writing, recognizing their differences and unique contributions to effective communication. It suggests a reorientation of teaching practices to broaden students' communicative-interactional skills, enabling them to meet social linguistic demands with competence.